Rossian Intuitionism without Self-Evidence? - David Kaspar (Philosophies, 2022)
The first phase of the recent intuitionist revival left untouched Ross’s claim that fundamental moral truths are self-evident. In a recent article, Robert Cowan attempts to explain, in a plausible way, how we know moral truths. The result is that, while the broad framework of Ross’s theory appears to remain in place, the self-evidence of moral truths is thrown into doubt. In this paper, I examine Cowan’s Conceptual Intuitionism. I use his own proposal to show how he arrives at a skeptical position on self-evidence. First, he completely ignores the kind of epistemic appraisal intuitionism has always rested on; second, he is committed to the Reasons View of prima facie duty, rather than to Ross’s Properties View; third, he holds that a commitment to self-evidence often comes with a commitment to metaphysically extravagant entities, which he calls Perceptualism; fourth, he scrutinizes only a part of the contemporary theory of self-evidence, overlooking the strengths of the theory when considered as a whole. Revealing these several points supports the conclusion that Cowan has not provided a viable variety of Rossian Intuitionism.